Pengaruh Persepsi Harga, Customer Value Dan Service Quality Terhadap Kepuasan Pelanggan (Studi Pada Pelanggan Jasa Travel Pelangi Antar Nusa) - Syamsul Arifin; M Hufron; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe purpose of this study was to determine and analyze the effect of perceived price, customer value and service quality simultaneously on customer satisfaction between Pelangi Travel Between Nusa Malang. To find out and analyze the effect of price perception on customer satisfaction on Pelangi Antar Nusa Malang Travel. To find out and analyze the influence of customer value on customer satisfaction at Pelangi Travel between Nusa Nusa Malang. To find out and analyze the effect of service quality on customer satisfaction in Pelangi Travel between Nusa Nusa Malang.This type of research uses Explanatori Reaserch. This research was conducted at Pelangi Travel, which is located at Jalan Sawahan No. 03, Turen Regency, Malang Regency. The population in this study is Malang City Pelangi Travel Services customers obtained from one month and an average of 450 customers every month.The results of this study indicate that Price Perception, Customer Value, Service Quality simultaneously has a significant effect on customer satisfaction. Keywords : Perception Price, Customer Value And Service Quality